The Profitability of Technical Stock Trading has Moved from Daily to Intraday Data - Stephan Schulmeister (Austrian Institute of Economic Research (WIFO), 2007)
This paper investigates how technical trading systems exploit the momentum and reversal effects in the S&P 500 spot and futures market. The former is exploited by trend-following models, the latter by contrarian models. In total, the performance of 2,580 widely used models is analysed. When based on daily data, the profitability of technical stock trading has steadily declined since 1960 and has become unprofitable over the 1990s. However, when based on 30-minutes data the same models produce an average gross return of 8.8 percent per year between 1983 and 2000. These results do not change substantially when trading is simulated over six subperiods. Those 25 models which performed best over the most recent subperiod produce a significantly higher gross return over the subsequent subperiod than do all models together. Over the out-of-sample period 2001-2006 the 2,580 models perform much worse than between 1983 and 2000. This result could be due to stock markets becoming more efficient or to stock price trends shifting from 30-minutes prices to prices of higher frequencies.
Keywords: 330; Technical trading; stock price dynamics; momentum effect; reversal effect; Finanzanalyse; Börsenkurs; Wertpapierhandel; USA